The Interface Influence in TiN/SiN x Multilayer Nanocomposite Under Irradiation - Uglov V. V. Vladimir Vasilievich; Safronov I. V.; Kvasov N. T. Nikolay Trafimovich; Remnev G. E. Gennady Efimovich; Shimanskii V. I. Vitali Igorevich (2018, 2018)
Title screen